Leaf morphological and genetic variation between Quercus rubra and Quercus ellipsoidalis: comparison of sympatric and parapatric populations - Oliver Gailing; Sarah Kostick; Oliver Caré; Sudhir Khodwekar (Annals of Forest Research, 2018)
Species boundaries in oaks are often not clear-cut, which is potentially a result of interspecific hybridization with trait introgression and phenotypic plasticity. Quercus rubra L. and Quercus ellipsoidalis E.J. Hill are two interfertile partially sympatric red oak species (section Lobatae) with different adaptations to drought. Quercus ellipsoidalis is the most drought tolerant of the North American red oak species and is characterized by deep tap roots, a shrubby growth and by deeply dissected leaves. Genetic differentiation between species is low for most molecular markers. However, one genic microsatellite in a CONSTANS-like (COL) gene, FIR013, was previously identified as outlier locus under strong divergent selection between species. In this study, we analyzed leaf morphometric traits in neighboring (parapatric) Q. rubra/Q. ellipsoidalis populations and in one sympatric population from the same region along an environmental gradient. Using multivariate statistics of leaf traits both species showed distinct bimodal frequency distributions for the first canonical discriminant function with some overlap in the phenotypic extremes, especially in the sympatric population. Leaf dissection traits showed strong and consistent differentiation between species in sympatric and parapatric populations, while differentiation for leaf size was lower in the sympatric population under more similar environmental conditions. Leaf phenotypes in F1 hybrids and introgressive forms suggested maternal effects and introgression of leaf traits between species. The association of outlier gene copy number at FIR013 with species-discriminating leaf traits in Quercus rubra can be a reflection of population differences since outlier gene copy number and population membership show significant collinearity. Similar environmental selection pressures on outlier alleles and leaf shape could also have resulted in this association. In future studies, segregating full-sib families could be used to test whether outlier alleles and associated genomic regions are indeed associated with leaf traits or other species-discriminating characters.